Convergent and predictive validity of the activities-specific balance confidence scales and balance recovery confidence scale, with regard to the falls efficacy scale-international: a cross-sectional study - Ting, Hazel Xu Teng; Ho, Jiaying; Ong, Peck Hoon; Young, William R.; Soh, Shawn Leng Hsien (Frontiers in Aging, 2025)
The purpose of this study was to determine the convergent validity between the Activities-specific Balance Confidence (ABC) Scale, Balance Recovery Confidence (BRC) Scale and Falls Efficacy Scale-International (FES-I), which are assessment tools used to measure the constructs of falls efficacy and concerns about falling. The study also investigated the predictive validity of ABC and BRC on concerns about falling. One hundred and thirty-one older adults (mean age of 73.5 years, SD 4.98) completed the three scales and self-reported their demographic data. 63.4% were female. The convergent validity between the ABC, BRC, and FES-I scales was investigated using Pearson correlation coefficients. Predictive validity was investigated using regression models. Findings indicated strong correlation between ABC and FES-I (r = −0.794, p < 0.001), and moderate correlation between BRC and FES-I (r = −0.587, p < 0.001) and ABC and BRC (r = 0.642, p < 0.001). ABC (R2 = 0.6279) was found to be a stronger predictor of FES-I than BRC (R2 = 0.3398). In conclusion, assessment tools for balance confidence, balance recovery confidence, and concerns about falling should be appropriately selected when studying the various constructs of interest, instead of using them interchangeably. Concerns about falling can also be further understood by exploring balance confidence and balance recovery confidence.